Genetic differentiation within and away from the chromosomal rearrangements characterising hybridising chromosomal races of the western house mouse (Mus musculus domesticus) - Förster, Daniel W.; Jones, Eleanor P.; Jóhannesdóttir, Fríða; Gabriel, Sofia I.; Giménez, Mabel Dionisia; Panithanarak, Thadsin; Hauffe, Heidi Christine; Searle, Jeremy B. (Springer, 2016)
Fil: Förster, Daniel W. Universidad de York. Departamento de Biología; Reino Unido.